What is needed by parents of constipated infants and toddlers: A cross-sectional study in China - Wang, Yuanyuan; Cao, Jinjin; Zhang, Weiying; Chen, Hongyu; Li, Mei; Liu, Zhifeng; Wang, Jianan (Frontiers in Pediatrics, 2023)
Background: Childhood functional constipation is a worldwide problem that affects the intestinal function of children and the quality of life of their families. Treatment and management of the disease need to be carried out at home by parents. Assessment of caregiving needs is an important link in planning and implementing intervention. This study aimed to assess the caregiving needs of parents of FC infants and toddlers. Methods: The researchers recruited convenience samples of parents from an outpatient pediatric constipation clinic of a children’s medical center. Totally 211 fathers/mothers were recruited. Nursing needs were measured by a questionnaire, and associations between nursing needs and potential factors were examined using multiple regression analysis. Results: The vast majority of participants (88.7%) expressed needs of receiving support from professionals, only 44 (20.85%) had obtained help from medical staff. Results showed statistically significant differences in parental education, place of residence, age of children, duration, frequency, difficulty of constipation, and fecal traits in nursing needs (p<0.05). The regression model explained 64.2% of the variance of nursing needs. Conclusions: Information needs were the major concern for parents, the unmet needs of parents should be addressed during treatment and care. When developing care plans and providing health education, it should be adjusted according to the specific conditions of the child and parents to improve the compliance of the parents with treatment and care.